Strange planet the sneaking, hiding, vibrating creature - Pyle, Nathan W. (Harper, an imprint of HarperCollinsPublishers, 2021)
"When the nearest star rises, Lifegiver has an exciting quest planned for Offspring! Follow along as they observe a strange creature that sneaks, hides, and vibrates around their house. Hilarity ensues as the blue beings try to mimic this talented creature"--
Keywords: Außerirdische Intelligenz; Humor; Katze; Erde; Cats / Juvenile fiction; Extraterrestrial beings / Juvenile fiction; Picture books; Earth (Planet) / Juvenile fiction; Extraterrestrial beings / Fiction; Cats / Fiction; Earth (Planet) / Fiction; Humorous stories; Bilderbuch